The Analysis of Figures of Speech of Emily Cooper in Emily in Paris Season 1 - Yusuf, Ferghi; Candra, Oktiva Herry; Savitri, Ayu Ida (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2024)
The research aims to elaborate on the types of figures of speech using the analysis of components of speech and to explain the functions of figures of speech in Emily in Paris Season 1. The researcher applies non-participant observation and note-taking techniques with purposive random sampling. In analyzing the collected data, the researcher applies the content analysis method. The findings show that Emily speaks 10 types of figures of speech, namely simile, metaphor, personification, metonymy, synecdoche, symbol, paradox, hyperbole, understatement, and irony. The employment of these speeches also reveals their function in the conversation of each character. The functions of figures of speech are to give imaginative pleasure, to bring additional imagery, to add emotional intensity, and to say much in a brief compass.